Effects of Mangosteen Peel Extract Microcapsules Supplemented in Diets on Intestinal Characteristics and Malondialdehyde of Cihateup Duck - Kusmayadi, Andri; Adriani, Lovita; Abun, Abun; Muchtaridi, Muchtaridi; Tanuwiria, Ujang Hidayat (Universitas Halu Oleo, 2023)
The aim of this study was to examine the effect of supplementation of mangosteen peel extract microcapsule which was encapsulated using maltodextrin from sugar palm starch (MPEM) on intestinal characteristics, and malondialdehyde of Cihateup duck. This study used 140 male Cihateup ducks, which were divided randomly into 7 groups of cages with different feed treatments. The T1 treatment consisted of only basal rations. The T2 treatment contained basal rations added with 50 ppm bacitracin. The treatment of T3 to T7 consisted of basal rations added by MPEM at the doses of 0.5, 1.0, 1.5, 2.0, and 2.5%, respectively. Data on intestinal characteristics, and malondialdehyde level were analyzed using a completely randomized design and if there were significant differences, further testing using DMRT method was performed. The results showed that MPEM treatment had a significant effect (P